2011
DOI: 10.1007/s00122-011-1640-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine genetic mapping of cp: a recessive gene for compact (dwarf) plant architecture in cucumber, Cucumis sativus L.

Abstract: The compact (dwarf) plant architecture is an important trait in cucumber (Cucumis sativus L.) breeding that has the potential to be used in once-over mechanical harvest of cucumber production. Compact growth habit is controlled by a simply inherited recessive gene cp. With 150 F(2:3) families derived from two inbred cucumber lines, PI 308915 (compact vining) and PI 249561 (regular vining), we conducted genome-wide molecular mapping with microsatellite (simple sequence repeat, SSR) markers. A framework genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 34 publications
2
59
0
Order By: Relevance
“…The first high-density cucumber genetic linkage map was constructed using data from the cucumber genome (Ren et al, 2009), and many molecular markers (such as ll,de,D,ss,u,bi,Ccu,and Tu) were found to be closely linked to genes governing important agronomic traits in cucumber (Yuan et al, 2008;Huang et al, 2009;Weng, 2010;Zhang et al, 2010a,b;Li et al, 2011). Complete genome genetic linkage maps containing more than 3.6 million loci have been developed by deep re-sequencing of 115 cucumber varieties (Qi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first high-density cucumber genetic linkage map was constructed using data from the cucumber genome (Ren et al, 2009), and many molecular markers (such as ll,de,D,ss,u,bi,Ccu,and Tu) were found to be closely linked to genes governing important agronomic traits in cucumber (Yuan et al, 2008;Huang et al, 2009;Weng, 2010;Zhang et al, 2010a,b;Li et al, 2011). Complete genome genetic linkage maps containing more than 3.6 million loci have been developed by deep re-sequencing of 115 cucumber varieties (Qi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CKX genes, causing a decrease in cytokinin levels, has been associated with inhibited shoot development and enhanced root development (Ha et al 2012). Sequence analysis by Li et al (2011) identified a 3 bp deletion in the coding region of the CKX7 gene in PI308915 relative to three accessions with standard stem length, prompting the suggestion that CKX7 is a candidate gene for the compact phenotype. Sequence comparisons with PI308916 have not yet been made for the other candidate genes in the cp region.…”
Section: Genetic Basis For the Compact Traitmentioning
confidence: 98%
“…Recent QTL analysis were performed by Li et al (2011) to locate the cp gene from PI308915, an accession with a similar phenotype to PI308916, also collected from Russia. The cp gene in PI308915 was localized to a narrow region of the long arm of cucumber chromosome 4 .…”
Section: Genetic Basis For the Compact Traitmentioning
confidence: 99%
“…CC3, SWCC8, and derived RILs were originally developed by Nanjing Agricultural University, China. Both CC3 (aka, Beijingjietou, north China fresh market type) and WI7200 (derived from PI 249561; Li et al, 2011) were cultivated cucumbers. SWCC8 and WI7167 are semiwild XIS cucumbers with short hypocotyls conferred by the sh1 allele.…”
Section: Plant Materialsmentioning
confidence: 99%
“…DNA extraction, PCR amplification, marker analysis, and gel electrophoresis followed Li et al (2011). Linkage analysis of the sh1 locus with molecular markers was performed with the Kosambi mapping function using JoinMap 4.0 with the threshold LOD score of 4.0.…”
Section: Fine Genetic Mapping Of Sh1 Locusmentioning
confidence: 99%